Elements of financial risk management - Christoffersen, Peter F. (Academic Press, 2003)
Value-at-Risk has emerged as the standard tool for measuring and reporting financial market risk. Currently, more than eighty commercial vendors offer enterprise or trading risk management systems that provide VAR-like measures. Risk managers are therefore often left with the daunting task of having to choose from this plethora of risk measures. While basic VAR textbooks describe average VAR situations, the vast majority of these situations are abnormal. Elements of Financial Risk Management focuses on implementation, especially recent techniques which facilitate "bridging the gap" between standard textbooks on risk and real-life risk management systems. This book will appeal to practitioners in the financial services and investment industries, as well as graduate students and advanced undergraduates who want exposure to these techniques. *Pinpoints key features of risk asset returns and captures them in tractable statistical models in the accompanying CD-ROM *Presents step-by-step approaches as a means to solve problems *Visible patterns in the data motivate the choices of tools, and when tools fall short, it presents the next tool